(untitled) (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2024)
Annotation This article, "The Importance of Religious Lexical Units in Literature," explores the critical role that religious language plays in enriching literary works.